Niveles de glicemia en personas mayores de 15 años del Mercado “Ex Mayorista”, calle el Albarracín de Trujillo, Marzo 2018 - Cueva Castillo, Katherin Guissell (2018)
The present report has as objectives give a know the results obtained from the determination of glycemia in people over 15 years of the market "Ex-Mayorista," street el Albarracín of Trujillo, participated 62 peoples of both sexes, for which before To extract the blood samples, the peoples were interviewed respectively. The blood samples were subjected to the analysis by the enzymatic method in serum or plasma, taking the spectrophotometer at 505nm . The normal glucose value is 70-115 mg / dL. The results obtained show that 59.67% of the population have serum glycemia values within normal values, 24.19% have hyperglycemia and 16.13% have hypoglycemia. Finally, for the analysis of the results we used the Chi square statistical method (X2) where glycemia levels were related to the IMC, age group and gender for which the hypothesis Ho and Ha was also raised, since the statistic was calculated is less than the statistic of the tables with the independent variables, by which it is not rejected and accepts the null hypothesis. It is concluded that there is no statistical significance with the data of body mass index, generated and age group